2021
DOI: 10.4028/www.scientific.net/msf.1016.1659
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Role of Intermetallic Phases in Microstructure of UFG Titanium VT8M-1 Alloy

Abstract: The paper studies the microstructure of two-phase ultrafine-grained titanium VT8M-1 alloy (Ti-5.7Al-3.8Mo-1.2Zr-1.3Sn), which was obtained by rotary swaging (RS). Parameters of the microstructure and the change of the phase elemental / chemical composition were investigated by scanning electron microscopy and transmission electronic microscopy. It was shown that the silicide particles like S2 - (Ti,Zr)6Si3 were precipitated in the process of rotary swaging. The influence of silicide precipitations on the chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…It appears they made an additional contribution via the precipitation mechanism of strengthening into the total strength after SPD processing ( Figure ). [ 43 ]…”
Section: Producing Ufg Structural States In Titanium Alloys By Spdmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears they made an additional contribution via the precipitation mechanism of strengthening into the total strength after SPD processing ( Figure ). [ 43 ]…”
Section: Producing Ufg Structural States In Titanium Alloys By Spdmentioning
confidence: 99%
“…In the third area, special attention is paid to enhancing the performance properties of UFG Ti alloys, such as low‐cycle and high‐cycle fatigue resistance, impact toughness, crack resistance, long‐term strength, and corrosion resistance. [ 5–8,40–43,45–53 ] Several recent studies have shown that the UFG structure formation in metals and alloys often noticeably reduces both the impact toughness and fracture toughness. For example, such a tendency was observed in nanostructured pure metals, such as Ni, Fe, and Ti, and the effect was attributed to the reduced capacity of UFG metals for strain hardening.…”
Section: Producing Ufg Structural States In Titanium Alloys By Spdmentioning
confidence: 99%
“…With regard to the VT8M-1 alloy, there are several studies in this direction [22][23][24][25]. In several works [22,23], ultrafine-grained workpieces with an average grain size of ~0.5 µm and a good combination of strength and ductility were obtained by equal-channel angular pressing (ECAP).…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 ] Our recent articles show that an UFG structure can be successfully produced in this alloy by equal‐channel angular pressing (ECAP), and this enables enhancing considerably the alloy's mechanical properties at room and operating temperatures. [ 18–21 ]…”
Section: Introductionmentioning
confidence: 99%
“…[18] Our recent articles show that an UFG structure can be successfully produced in this alloy by equal-channel angular pressing (ECAP), and this enables enhancing considerably the alloy's mechanical properties at room and operating temperatures. [18][19][20][21] The aim of this work is to study the mechanical behavior of the VT8M-1 alloy processed by ECAP during compression tests in a temperature range of 650-800 C, as well as to evaluate the degradation of the UFG structure and its response to the mechanical properties of the billet during a physical experiment imitating isothermal forging at 700 C. Corporation (Russia) was selected as the material for the study. The rod's chemical composition is presented in Table 1.…”
Section: Introductionmentioning
confidence: 99%